2015
DOI: 10.1590/1414-431x20144189
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy with tamoxifen reduces plasma levels of NT-B-type natriuretic peptide but does not change ventricular ejection fraction after chemotherapy in women with breast cancer

Abstract: The objective of this study was to evaluate the effect of tamoxifen on the plasma concentration of NT-pro-B-type natriuretic peptide (NT-proBNP) in women undergoing chemotherapy for breast cancer and to correlate changes in NT-proBNP with the left ventricular ejection fraction (LVEF). Over a period of 12 months, we followed 60 women with a diagnosis of breast cancer. The patients were separated into a group that received only chemotherapy (n=23), a group that received chemotherapy + tamoxifen (n=21), and a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In the present study, patients with breast cancer who were positive for ER or HER2 may have additionally received tamoxifen and Herceptin treatment. Previous studies have suggested that tamoxifen has a protective effect on cardiac function (31), whereas Herceptin treatment may be cardiotoxic (32). However, there was no such evidence of either tamoxifen-mediated cardiac protection or Herceptin-mediated cardiotoxicity in the study, in agreement with other previous studies (33,34).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, patients with breast cancer who were positive for ER or HER2 may have additionally received tamoxifen and Herceptin treatment. Previous studies have suggested that tamoxifen has a protective effect on cardiac function (31), whereas Herceptin treatment may be cardiotoxic (32). However, there was no such evidence of either tamoxifen-mediated cardiac protection or Herceptin-mediated cardiotoxicity in the study, in agreement with other previous studies (33,34).…”
Section: Discussionsupporting
confidence: 91%
“…These data suggested that fenofibrate had a minor effect on the increase in adiponectin in DOX-triggered cardiotoxicity. In addition, a previous study reported that the level of pro-BNP was increased by chemotherapy 44 . In our study, DOX-induced increases in circulating BNP and pro-BNP were also attenuated by fenofibrate, and this effect was abolished by L-NAME.…”
Section: Discussionmentioning
confidence: 96%
“…In this case, the data were significantly higher than those for patients receiving tamoxifen. [ 19 ] These findings encourage the possibility that such subclinical changes are predictive of cardiac damage in the future.…”
Section: Discussionmentioning
confidence: 83%